An ultrasonographic evaluation of masseter muscle thickness in different dentofacial patterns - Ajit K Rohila; Vijay P Sharma; Pradeep K Shrivastav; Amit Nagar; Gyan P Singh (Wolters Kluwer Medknow Publications, 2012)
Objectives: The aim of this study is to compare the masseter muscle thickness in different vertical dentofacial patterns and identify the possible sexual dimorphism and also to correlate masseter muscle thickness with craniofacial morphology using cephalometric parameters. Materials and Methods: The masseter muscle thickness was measured using ultrasonography in 60 subjects (30 females and 30 males). Standardized lateral and posteroanterior cephalograms were taken to determine the facial morphology. The subjects were divided into three vertical pattern groups (I, II, and III) according to their Jarabak ratio: hypodivergent ( n = 20), normodivergent (n = 20), and hyperdivergent (n = 20). The sample was further subdivided into males and female subgroups. Results: Masseter muscle thickness relaxed (MMTR) in hypodivergent group was 13.94 ± 1.51. Mean value of MMTR in normodivergent group was 12.53 ± 1.21 and the MMTR in hyperdivergent group was 11.13 ± 1.18. The mean value of masseter muscle thickness contracted (MMTC) in hypodivergent group was 15.46 ± 1.33. Mean value of MMTC in normodivergent group was 13.81 ± 1.38 and the mean value of MMTC in hyperdivergent group was 12.27 ± 1.26. MMTC showed a significant, negative correlation with mandibular plane angle and gonial angle. Posterior facial height, symphysis width, intermolar width of maxillary first molars, maxillary width, and facial width (bizygomatic width) showed significant ( P < 0.05 or P < 0.01) positive correlation. Conclusion: The masseter muscle thickness varied among the three vertical dentofacial patterns and sexual dimorphism also existed except in the hyperdivergent group. Masseter muscle thickness was found to be negatively correlated to vertical facial pattern and positively associated with transverse craniofacial morphology.